The effect of credit risk on the cash dividend policy of banks listed on the Palestine Stock Exchange - Saleem Khoffash; Bahaa Subhi Awwad (Banks and Bank Systems, 2025)
This study aims to examine the impact of credit risk on the cash dividend policies of banks listed on the Palestine Stock Exchange from 2015 to 2021. Credit risk is measured using the ratio of non-performing loans to total loans and the ratio of total loans to total assets as key indicators. The study also explores the effect of other factors, such as return on assets, return on equity, profit margin, bank size, and bank age, as additional determinants of dividend policies. OLS with multiple regression analysis was used to evaluate the relationship between the independent variables and the dependent variable. The results showed no statistically significant effect of credit risk on dividend distributions, indicating that financial performance indicators play a more crucial role in dividend decisions. A weak positive relationship between credit risk ratios and dividend distributions was observed, but it was not statistically significant, suggesting that credit risk is not a fundamental determinant of dividend policies. These findings align with signaling theory, suggesting that dividends in the Palestinian banking sector do not clearly reflect credit risk due to market inefficiencies. The study highlights the importance of financial indicators in determining dividend policies, the stability of dividend distributions in older banks, and the need for strong regulatory frameworks, while recommending further research on other determinants such as ownership structure and digital transformation. AcknowledgmentsWe sincerely thank Palestine Technical University – Kadoorie for their generous financial and moral support throughout the course of this research.